The Effect of Work Motivation on Employee Performance: The Mediating Role of Job Satisfaction in a Local Government Protocol Office - Hansyah, Fajari; Riswan (International Journal of Economics, Business and Innovation Research, 2026)
Employee performance plays a critical role in ensuring the effectiveness of public sector organizations, particularly government protocol offices that demand high levels of professionalism, responsiveness, and time accuracy. This study aims to examine the effect of work motivation on employee performance, the effect of work motivation on job satisfaction, the effect of job satisfaction on employee performance, and the mediating role of job satisfaction in the relationship between motivation and performance. This study employed a quantitative explanatory approach using a census survey of 50 employees at the Protocol Office of West Lampung Regency, Indonesia. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3.0. The results indicate that work motivation has a positive and significant effect on employee performance and job satisfaction. Job satisfaction also significantly influences employee performance. Furthermore, job satisfaction partially mediates the relationship between motivation and employee performance. These findings support Herzberg’s Two-Factor Theory, emphasizing the importance of motivational factors in shaping job satisfaction and performance in public sector organizations. Practically, this study suggests that government institutions should integrate motivational strategies and job satisfaction management to enhance sustainable employee performance.